The Spatial Politics of the Tonle Sap: A Multi-Scale Analysis of Conservation and Development Challenges - Sithirith, Mak (Qeios, 2024)
Key resources of Tonle Sap Lake are fish, biodiversity and natural resources. Its governance has been casted as a central pillar in the development of Cambodia. Although there are considerable literatures and documents, supporting the protection and conservation of the lake, there are also policies and development frameworks promoting hydropower investments and infrastructure developments, affecting the TSL. Accordingly, this study questions how the water, fishery, and biodiversity and infrastructure developments are embedded in the conservation and developments of TSL. In answering this question, the study conducts the literature reviews and case studies in the Tonle Sap Biosphere Reserves, employing the political ecology approach. It concludes that TSL is food producing engines of Cambodia, the heartbeats of the Mekong River Basin, and a global biodiversity hotspot. The protection and conservation of the lake bring benefits to all at national, regional and global levels, but the complex interplay of actors, arranged at various scales and levels, has collectively created the challenges facing the lake, giving rise to confrontation between the conservation and hydropower, questions about the long-term sustainability of its resources and the livelihoods that depend upon it.